Identifikasi Plant Growth Promoting Rhizobacteria pada Rizosfer Bambu Duri dengan Gram KOH 3% - Muhammad Yusril Hardiansyah; Yunus Musa; Abdul Mollah Jaya (Agrotechnology Research Journal, 2020)
Plant Growth Promoting Rhizobacteria is a group of microorganism that is able to increase plant growth and yield through reactions in the soil, but the large number of microorganisms contained in PGPR's rhizosphere from thorn bamboo make it difficult to know which bacteria are the most dominant and most active in influencing plants. This study aimed to determine the effect of using the 3% gram KOH test method in identifying PGPR bacteria from the thorn bamboo rhizosphere. This test was carried out at the Biofertilizer and Potential Microbial Laboratory, Faculty of Agriculture, Universitas Hasanuddin from October-December 2019. The testing methods include making microorganism growing media, pouring media, planting bacteria with the scatter and scratch methods, also the gram reaction test using KOH 3%. The results obtained the use of the 3% gram KOH test method in the scatter method showed there were 2 samples that have mucus with a percentage of 40%, while in the scratch method showed all samples have mucus with a percentage of 100% so that the use of the 3% gram KOH test method has an optimum effect in detecting microorganisms especially in identifying plant growth promoting rhizobacteria.